Perencanaan Ulang Tata Letak Pada Ritel Lestari Kota Bogor - Inayatul Maula; Rohimah Rohimah; Khairunnisa Salsabila; Talitha Azalia; Revian Alif Maulana (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2024)
The Ritel business in Indonesia is growing and increasing every year because it is considered a promising investment with great potential for significant profits. This study aims to understand and evaluate the layout of Retail Lestari's business. The method used in analyzing the data is the Activity Relationship Chart (ARC) and Total Closeness Rating (TCR) method. Based on the results of the Activity Relationship Chart (ARC) analysis of Ritel Lestari, the facility prioritized for first construction is the cashier, as the cashier has the highest Total Closeness Rating (TCR) value of 76. Therefore, to facilitate the operational process, the placement of other facilities is prioritized based on their highest relationship values to the warehouse to be in close proximity.